Spatialising degrowth in Southern cities: Everyday park-making for (un)commoning. (May 2023) - Anantharaman, Manisha; Sahakian, Marlyne; Saloma, Czarina
Answering the call in this special issue to spatialise degrowth studies beyond the Global North, this paper examines practices of 'park-making' in Chennai and Metro Manila as a potential degrowth pathway. Parks in the coastal mega cities of Metro Manila and Chennai can be seen as relics of a colonial era, and spaces coherent with capitalist, growth-oriented and consumerist logics. At the same time, however, they become spaces that prefigure alternative ways of organising social life in the city based upon values of conviviality, care and sharing. Using qualitative methods of analysis, this paper examines what practices people engage with to satisfy their everyday needs in parks, but also the dynamics of exclusion and contestation that play out in these spaces. In doing so, we evaluate when and under what conditions park-making supports practices of de-growth and commoning beyond consumerist culture. Both commoning and uncommoning practices are detailed, revealing the role of provisioning systems that lead to the satisfaction of needs for some at the expense of others. Further, writing from cities that are highly unequal, and where the basic needs of many are yet to be met, we assert that understanding how degrowth manifests in these contexts can only be revealed through a situated urban political ecology approach. Spatialising degrowth in cities of the Global South should start with a focus on everyday practices, study power relationally and explore the scope for a radical incrementalism.